2006
DOI: 10.1111/j.1463-6395.2006.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The basicoxal gland, a new exocrine structure in poneromorph ants (Hymenoptera, Formicidae)

Abstract:  AbstractBillen, J. and Ito, F. 2006. The basicoxal gland, a new exocrine structure in poneromorph ants (Hymenoptera, Formicidae). -Acta Zoologica (Stockholm) 87 : 291-296The tegumental epithelium of the outer dorsolateral region in the proximal part of the coxae in the mid-and hindlegs of both workers and queens of the ants Odontomachus rixosus and O. simillimus is differentiated into a conspicuous and hitherto unknown exocrine gland. The glandular cells display a clear microvillar differentiation of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…For this purpose, an impressive muscular supply surrounded the glands reservoir. Billen and Ito 16 showed that the secretion was forced into the venom gland duct by muscle contraction; it was carried straight through the sting and injected it into the victim. In the southeast Asian Stenogastrinae, the secretion of Dufour's gland was used in larval nutrition and nest defense.…”
Section: Karsai and Wenzelmentioning
confidence: 99%
“…For this purpose, an impressive muscular supply surrounded the glands reservoir. Billen and Ito 16 showed that the secretion was forced into the venom gland duct by muscle contraction; it was carried straight through the sting and injected it into the victim. In the southeast Asian Stenogastrinae, the secretion of Dufour's gland was used in larval nutrition and nest defense.…”
Section: Karsai and Wenzelmentioning
confidence: 99%
“…Its presence in all the species examined and its occurrence in the three leg pairs and in both workers and queens indicate that it is probably a common structure with a general function. Its appearance closely resembles that of the basicoxal gland (Billen and Ito 2006) and of the glandular epithelium in the proximal part of the basitarsus (see figure 11 in Billen 1997). The position of these glands in all three cases is in the articulation region with the next leg segment or thorax, which is suggestive for a function of producing lubricant substances (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Such function finds additional support in the precise anatomical position, as the trochanter gland occurs ventrally, which is where the up‐and‐down movement between the coxa and the trochanter is maximal, whereas the basicoxal gland occurs dorsally (which likewise is where the mainly anteroposterior coxal movements against the corresponding thoracic cavity are maximal). The basicoxal gland is absent in the forelegs, which can be explained by the limited movements between the thorax and the foreleg coxae (Billen and Ito 2006). The manoeuvrability between the coxa and trochanter, however, is high in the three leg pairs, and helps explain the presence of the trochanter gland in all legs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of glandular epidermis is common in eussocial Hymenoptera, and it is associated with the secretion of pheromones or wax used for nest building (Guerino and CruzÐLandim 2003, Eelen et al 2004, Billen and Ito 2006, MarquesÐSilva et al 2006). Mated queens of Ectatomma tuberculatum (Olivier) (Hymenoptera: Formicidae) have glandular epidermis in all body segments (Hora et al 2010), which is probably true for H. angulosus.…”
Section: Discussionmentioning
confidence: 99%